Systematics and Phylogenetic Relationships of New Zealand Benthic Octopuses (Cephalopoda: Octopodoidea) - Ibáñez, Christian M.; Fenwick, Mark; Ritchie, Peter A.; Carrasco, Sergio A.; Pardo-Gandarillas, M. Cecilia (Frontiers in Marine Science, 2020)
The systematics of the New Zealand octopods have only been reviewed twice in the last 100 years. In these revisions many species have been provisionally classified in the genus Octopus. Recent genetic studies have synonymized some New Zealand species with octopuses from other regions. The present study investigates the systematics and phylogeny of octopuses from New Zealand using eighty eight specimens, three mitochondrial genes (16S rRNA, cytochrome c oxidase subunit I and cytochrome c oxidase subunit III) and one nuclear gene (Rhodopsin). Forty-four new octopod DNA sequences (belonging to 13 species) were included, adding to the 83 existing sequences from GenBank. All sequences were used to generate phylogenetic trees based on Maximum Likelihood (ML) and Bayesian inference (BI), with a data set composed by 97 species, including octopod sister groups and Vampyroteuthis infernalis as an outgroup. Gene tree and species delimitation analyses revealed a distinct genetic difference between two sympatric Graneledone subspecies, which we propose as valid species. Muusoctopus tangaroa is a sister species of M. thielei from Kerguelen; while Enteroctopus zealandicus forms a clade with E. megalocyathus from South America and E. dofleini from the North Pacific. Similarly, Octopus campbelli, O. huttoni and O. mernoo form a monophyletic group with Robsonella fontanianus from South America, Scaeurgus unicirrhus from the Atlantic and O. pallidus from Australia. Pinnoctopus cordiformis is close to Grimpella thaumastochier and several species of Octopus sensu lato as in previous phylogenetic studies. This study suggests that octopuses from New Zealand have different phylogenetic and biogeographic origins and represent independent radiations into this region.